ANTECEDENTS OF BUDGETARY PARTICIPATION: ENHANCING EMPLOYEESâ JOB PERFORMANCE - Nikmah, Fatmawati (Jurnal Studi Akuntansi Indonesia, 2012)
This research investigated the antecedent budgetary participation (need for achievement and work attitude), then assess the impact on employeesâ job performance. The data were obtained using questionnaires that distributed to respondents. Seventy two respondents were chosen as samples and path analysis was used as techniques to analyze the data. The result of this research showed that need for achievement has significant positive association with budgetary participation. However, the result found that there is no significant association between work attitude and budgetary participation. Furthermore, the researcher found that budgetary participation had a significant positive association with job performance (e.i managerial performance). The researcher concludes that when employees have a higher need for achievement, they will tend to higher participation in budgetary process, and this condition will enhance employeesâ job performance. Here, budgetary participation acted as mediating variable between need for achievement and job performance.